Sistem Informasi Akuntansi Sumbangan Pembinaan Pendidikan (SPP) Berbasis Website Menggunakan Metode Waterfall Pada SMKS Elim Kalimantan - Sabaruddin, Raja; Murni, Sri; Nugraha, Wahyu; Linawati, Safitri; Junia Erytika, Liva (Jurnal Sistem Informasi Akuntansi, 2022)
SMKS Elim Kalimantan does not yet have a good information system from the payment process for the Educational Development Contribution (SPP) which is still manual and there are frequent data recording errors between the main book or the payment report book for the Educational Development Contribution (SPP) and the student committee contribution card. To overcome the problems faced by the Elim Kalimanatan Vocational School, especially in the payment of the Educational Development Contribution (SPP), a web-based accounting information system for the Educational Development Contribution (SPP) payment is needed this is expected to help deliver information and facilitate the implementation of data processing on the payment of Educational Guidance Contributions (SPP) at SMKS Elim Kalimantan. The research method used is the waterfall type SDLC method which includes the planning, application development, testing and application stages. This application can help deliver information and facilitate the implementation of data processing on the payment of Educational Development Contributions (SPP) at SMKS Elim Kalimantan every month.